Eriophyoid mites (Acari: Eriophyoidea) on Trochodendron aralioides (Trochodendraceae) from Taiwan - Huang, Kun-Wei (Zootaxa, 2006)
In this work, three new species of vagrant mites on Trochodendron aralioides in Taiwan are described and illustrated. They are: Sierraphytoptus taiwanensus sp. nov., Abacarus aralioidus sp. nov. and Diptilomiopus aralioidus sp. nov.